Profiling high-range speeding offenders: Investigating criminal history, personal characteristics, traffic offences, and crash history. (January 2015) - Watson, B.; Watson, A.; Siskind, V.; Fleiter, J.; Soole, D.
Highlights: Queensland speeding offences ( N = 84, 456) were used to profile repeat high-range offenders. Significant differences found for age, gender, licence class and traffic offences. Crash and criminal history also significantly higher for repeat high-range offenders. Results that speeding offenders are not an homogeneous group. Tailored countermeasures are needed for this high-risk road user group. Abstract: This paper reports profiling information for speeding offenders and is part of a larger project that assessed the deterrent effects of increased speeding penalties in Queensland, Australia, using a total of 84, 456 speeding offences. The speeding offenders were classified into three groups based on the extent and severity of an index offence: once-only low-rang offenders ; repeat high-range offenders ; and other offenders . The three groups were then compared in terms of personal characteristics, traffic offences, crash history and criminal history. Results revealed a number of significant differences between repeat high-range offenders and those in the other two offender groups. Repeat high-range speeding offenders were more likely to be male, younger, hold a provisional and a motorcycle licence, to have committed a range of previous traffic offences, to have a significantly greater likelihood of crash involvement, and to have been involved in multiple-vehicle crashes than drivers in the other two offender types. Additionally, when a subset of offenders' criminal histories were examined, results revealed that repeat high-range speeding offenders were also more likely to have committed a previous criminal offence compared to once only low-range and other offenders and that 55.2% of the repeat high-range offenders had a criminal history. They were also significantly more likely to have committed drug offences and offences against order than the once only low-range speeding offenders, and significantly more likely to have committed regulation offences than those in the other offenders group. Overall, the results indicate that speeding offenders are not an homogeneous group and that, therefore, more tailored and innovative sanctions should be considered and evaluated for high-range recidivist speeders because they are a high-risk road user group.